1991
DOI: 10.1113/expphysiol.1991.sp003487
|View full text |Cite
|
Sign up to set email alerts
|

MDL 72222 (a selective 5‐HT3 receptor antagonist) prevents stimulation of intrapulmonary C fibres by pulmonary embolization in anaesthetized rabbits

Abstract: SUMMARYWe have investigated the effects of the intravenous administration of 5-hydroxytryptamine upon the discharge frequency of pulmonary stretch receptors, irritant receptors and C fibres. Only C fibres were stimulated by this autacoid. MDL 72222 a selective 5-HT3 receptor antagonist blocks the C fibre stimulation by 5-hydroxytryptamine. It also blocks the C fibre response to miliary pulmonary embolism. These data confirm the hypothesis that 5-hydroxytryptamine is the humoral link between pulmonary embolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Earlier evidence revealed that MDL precluded serotonin-induced chemoexcitation of carotid body chemoreceptors in cats and reflex apnea provoked by 5HT 3 agonist in rats (Kirby and McQueen, 1984;McQueen et al, 1998). Qualitatively similar results were obtained in rabbits since a large dose of MDL attenuated tachypnoea in experimental pulmonary embolism, reduced respiratory effects of the intravenous 5HT and blocked stimulation of vagal C-fibers endowed with 5HT 3 receptors Kay and Armstrong, 1990;Kay and Armstrong, 1991). It is of note that in our study, respiratory reflex responses triggered by excitation of 5HT 3 receptors were potently, completely inhibited by MDL.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Earlier evidence revealed that MDL precluded serotonin-induced chemoexcitation of carotid body chemoreceptors in cats and reflex apnea provoked by 5HT 3 agonist in rats (Kirby and McQueen, 1984;McQueen et al, 1998). Qualitatively similar results were obtained in rabbits since a large dose of MDL attenuated tachypnoea in experimental pulmonary embolism, reduced respiratory effects of the intravenous 5HT and blocked stimulation of vagal C-fibers endowed with 5HT 3 receptors Kay and Armstrong, 1990;Kay and Armstrong, 1991). It is of note that in our study, respiratory reflex responses triggered by excitation of 5HT 3 receptors were potently, completely inhibited by MDL.…”
Section: Discussionsupporting
confidence: 71%
“…It has been shown that the respiratory effects of 5HT are due to stimulation of pulmonary C fibers endings, endowed with 5HT 3 receptors in rabbits Kay and Armstrong, 1991). Moreover, 5HT 2 and 5HT 3 receptors are present on sensory cell bodies in the nodose ganglion in this species (Christian et al, 1989).…”
Section: Introductionmentioning
confidence: 98%
“…Experimental pulmonary embolism in rabbits leads to serotonin release (presumably from platelets) that in turn stimulates 5‐HT3 receptors on intrapulmonary vagal C‐fibres causing reflex tachypnoea (Armstrong & Kay, 1990). Intrapulmonary entrapment of activated platelets leads to reflex‐mediated circulatory collapse in part due to 5‐HT3 receptor‐mediated afferent nerve activation (Kay & Armstrong, 1991). Based on present findings, it would appear that these processes probably involve the activation of nodose more than jugular intrapulmonary vagal C‐fibres.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the introduction, serotonin likely stimulates C fibre sensory afferents. Administered into the pulmonary circulation, it excites vagal C fibres endowed with 5HT 3 receptors [14,17,23] and increases the activity of the serotonergic system throughout the whole vagal pathway to the nucleus of the solitary tract [10]. In the present experiments, disruption of this afferent input from the lungs at the midcervical level reduced both the size and duration of the ventilatory responses to serotonin, but did not qualitatively alter the pattern of the respiratory sequelae.…”
Section: Discussionmentioning
confidence: 62%
“…This constellation of cardiorespiratory responses has been termed pulmonary chemoreflex [6]. It has been shown that the respiratory effects of 5HT are due to stimulation of pulmonary C fibre endings, endowed with 5HT 3 receptors [3,17] in cats and rabbits; however, 5HT is acting at reduced level following midcervical section of the vagi [8]. Moreover, apnoea induced by injecting 5HT into the common carotid artery is abolished by supranodose vagotomy in cats [4,16].…”
Section: Introductionmentioning
confidence: 99%